MOTIVASI DAN BUDAYA BERBAHASA INGGRIS MASYARAKAT DAERAH TUJUAN WISATA TERHADAP PERKEMBANGAN BAHASA ANAK DI TINGKAT SLTA (STUDI KASUS: DESA LAGUNDRI-DESA SORAKE- DESA BAWOMATALUO) - Bestari Laia; Eka Periaman Zai (Jurnal Education and Development, 2020)
Mastering English is the same as making life easier for opportunities to work and communicate with other people around the world. Mastering English is not an easy thing for beginners but with high motivation it can be achieved. English is needed anywhere, especially tourist destinations. South Nias is one of the areas known to have traditional houses, stone jumping, war dance, white sand, big waves, traditional souvenirs, and so on. This place is often visited by local tourists and even foreign tourists. Of course, the surrounding community is expected to be able to speak English well. The methodology in this study is a qualitative research method. The instrument in this study was a questionnaire in the form of a questionnaire. Data collection was carried out in September 2020. The research subjects were high school students in three villages, namely Bawomataluo Village, Lagundri Village and Sorake Village. Based on the results of the research and discussion, it can be concluded that the motivation to speak English is caused by internal and external factors. Internal factors are appeared because of the individual's desire to have achievements and responsibilities in its life. Meanwhile, esternal factors are appeared because of external roles, which also determine a person's behavior in life. There are 3 (three) motivations that appear in tourist destinations, namely because of the need, hope and condition; English-speaking culture in tourist destination is based on the emergence of habits of interacting and communicating with each other so that it becomes a habit that requires mastering; Motivation and English speaking culture in tourist destination areas for language development of children at the senior high school level are very important to be able to interact and communicate with visitors, especially tourists who travel to tourist destinations. Suggestions, the public must be aware that one part of service to tourists is being able to communicate in their language or the language they know; The presence of English language institutions / communities / courses / training in tourist destinations are very beneficial for the community in general and children in particular.